Transanal Endorectal Pull-Through Procedure for patients with Hirschsprung`s Disease: A prospective study - Abdul-Ghafoor, Bilal H.; Abdullah, Ali F.; Al-Amery, Makke A. F. (Journal of the Faculty of Medicine Baghdad, 2016)
Back ground: Hirschsprung`s disease is a common problem among pediatric population, many procedures had been implemented in the treatment with different results. In the last decades one stage transanal endorectal pullthrough (TEPT) had come into the stage as a minimal invasive choice for such condition with good results. Objectives: To evaluate the feasibility and safety of TEPT procedure among pediatrics in a tertiary pediatric surgery center in Iraq. Patients and Methods: A prospective study was conducted on 11 patients with Hirschsprung’s disease, attending Central Teaching Hospital of Pediatrics for the period from March 2007 till August 2014. Their ages were ranging from 1 month - 12 years. All cases had diverting colostomy and leveling biopsy. The aganglionic segment was confined to the rectum and rectosigmoid junction. TEPT was done to all cases with closure of colostomy 6-8 weeks after pullthrough. The patients were followed up for a period of 6 months-4 years. Results: The study was conducted on 11 patients with a mean age of (33.7 ± 43.4 months); the male to female ratio was 9:2. Regarding the level of aganglionosis, it was confined to the rectum in 4 cases, while it reached the rectosigmoid junction in 7 cases. The mean operating time was (115.4 ± 23.5 minutes), and the mean volume of blood loss was (37.3 ± 17.6 ml). The average length of resected aganglionic segment was (13.9 cm). There is no conversion to laparotomy in any case. Complications developed in two cases one with perianal excoriation and the other develop postoperative enterocolitis. Conclusion: Transanal Endorectal Pull-Through operation for Hirschsprung’s disease is feasible and safe, and it can be performed successfully in all ages of children with good results avoiding transabdominal exploration.